T-bet Expression in Peripheral Th17.0 Cells Is Associated With Pulmonary Function Changes in Sarcoidosis - Arger, Nicholas K.; Machiraju, Siddharth; Allen, Isabel E.; Woodruff, Prescott G.; Koth, Laura L. (Frontiers in Immunology, 2020)
Background: Interferon-gamma (IFN-γ) is a key mediator of sarcoidosis-related granulomatous inflammation. Previous findings of IFN-γ-producing Th17 cells in bronchoalveolar lavage fluid from sarcoidosis patients invokes the transition of Th17.0 cells to Th17.1 cells in the disease’s pathogenesis. Since the T bet transcription factor is crucial for this transition, the goal of this study was to determine if T bet expression in Th17.0 cells reflects the extent of granulomatous inflammation in sarcoidosis patients as assessed by clinical outcomes. Methods: Using a case-control study design, we identified two groups of sarcoidosis subjects (total N=43) with pulmonary function tests (PFTs) that either 1) changed (increased or decreased) longitudinally or 2) were stable. We used flow cytometry to measure the transcription factors T bet and RORγt in Th1, Th17.0, and Th17.1 cell subsets defined by CCR6, CCR4 and CXCR3 in blood samples. We compared the percentages of T bet+ cells in RORγt+Th17.0 cells (defined as CCR6+CCR4+CXCR3-) based on subjects’ PFT group. We also assessed the relationship between the direction of change in PFTs with the changes in %T bet+ frequencies using mixed effects modeling. Results: We found that T bet expression in subjects’ RORγt+Th17.0 cells varied based on clinical outcome. The T bet+ percentage of RORγt+Th17.0 cells was higher in the cases (subject group with PFT changes) as compared to controls (stable group) (27% vs. 16%, p = 0.0040). In comparisons before and after subjects’ PFT changes, the T bet+ frequency of RORγt+Th17.0 cells increased or decreased in the opposite direction of the PFT change. The percentage of these T bet+ cells was also higher in those with greater numbers of involved organs. Serum levels of interferon-γ-induced chemokines, CXCL9, CXCL10, and CXCL11, and whole blood gene expression of IFN-γ-related genes including GBP1, TAP1, and JAK2 were independently positively associated with the T bet+ frequencies of RORγt+Th17.0 cells. Conclusions: These data suggest that expression of T bet in Th17.0 cells could reflect the extent of granulomatous inflammation in sarcoidosis patients because they represent a transition state leading to the Th17.1 cell phenotype. These findings indicate that Th17 plasticity may be part of the disease paradigm.